PENGARUH KELAS ONLINE TERAPI PIJAT BAYI TERHADAP KUALITAS TIDUR BAYI USIA 3-12 BULAN PADA MASA PANDEMI COVID 19 - Mutiara Dwi Yanti (Jurnal Inovasi Kesehatan Masyarakat, 2022)
Sleep needs are not only seen from the aspect of quantity but also quality. With good quality sleep, the baby's growth and development can be achieved optimally. One way that can be used to meet these needs is with Baby Massage . The researcher conducted interviews with 10 mothers of babies, it was found that on average the baby's mothers never massaged their babies. This study aims to analyze the effect of the Online Baby Massage class on the sleep quality of babies aged 3-12 months during the covid 19 pandemic at the Poskesdes, Paya Laba Village, East Kluet District, south aceh district. This type of research is pre experimental design with one group pretest- posttest design. The study population is infants aged 3-12 months. The research sample of 15 infants aged 3-12 months, in total sampling. Independent Variable baby massage and dependent variable sleep quality infants aged 3-12 months. Research Instrument using a questionnaire. Processing of data statistical test Wilcoxon The results showed that the sleep quality of babies aged 3-12 months before being given baby massage was almost half enough, namely as many as 8 respondents (53.3 %) and the sleep quality of babies aged 3-12 months after baby massage was mostly good, as many as 8 respondents. (53,3 %) . A statistical test of wilcoxon showed that the significant value of p value = 0.001 < a (0.05), so that H 1 is accepted. The conclusion of research which means there Effect Class Online Massage Therapy Baby To Sleep Quality Ages 3-12 months Babies In The Covid-19 Ponkesdes Paya Laba Village, East Kluet District, south aceh district.